ANALISA PERHITUNGAN LINK BUDGET SISTEM KOMUNIKASI ANTAR PELABUHAN MENGGUNAKAN KANAL HF - Lucita Spic Arsasiwi; Julius Maju Bonatua; Hani’ah Mahmudah; Ari Wijayanti (SENTIA 2016, 2016)
Indonesia is the world largest archipelagic state where its sea territoty is very broad, stretches from Sabang to Merauke. Regarding that, Indonesia requires an effective inter-island communication system. Moreover, the need for wireless communications is very high so it requires a wireless communication network planning. In the process for planning a maritime wireless communication system, it needed a link budget calculation. Link budget calculation has an important role in order to design communication networks so it can achieve optimum results and efficient both in terms of technical reliability and cost. In relation to that, this paperdiscuss about link budget calculation of communication system between Port of Tanjung Perak Surabaya and Port of Soekarno-Hatta Makassar using High Frequency (HF). High Frequency Radio (HF Radio) widely used for long distance communication. HF Radio communication in maximum condition was affected by many things, such as location, frequency and transmitting time. Beside that, it can also be affected by interference of ionosphere. This paper discuss about calculation of received power with using three types of antenna transmitters and three types of antenna receiver. The smallest receiving power is when HF Radio communication being used in elevation angle 18,1° at noon and 29,5° at night. The results of this calculation can be said that the best transmitter antenna and receiver antenna is pairing of CV430B and 258F-1 because its margin value is the best among the other antennas.